The Effect of Extreme Economic Assistance on Community Income in Kaway XVI District, West Aceh Regency (Case Study of 6 Villages in Kaway XVI District) - Melda, Ade; Wahyuningsih, Yayuk Eko; Sani, Sri Rosmiati; Syahril; Yasrizal (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Extreme economic assistance is assistance channeled by bappeda to the poor in Kaway XVI District with rupiah units in 2023. Ex- treme economic assistance is a form of financial assistance and re- sources provided to individuals, households, or countries experi- encing a severe economic crisis or emergency situation that threat- ens their lives and livelihoods. Assistance in the form of finances and resources provided to individuals, households, or countries ex- periencing severe economic crises or emergency situations that threaten their lives and livelihoods. The purpose of this study is to determine the effect of extreme economic assistance on commu- nity income before and after the assistance. The analysis used is simple regression analysis with dummy, to determine the linear re- lationship between one independent variable (X) and one depend- ent variable (Y). Based on the results of the t test Extreme Eco- nomic Assistance obtained a t-count value smaller than the t table, so extreme economic assistance has a positive but insignificant re- lationship to community income in Kaway XVI District, West Aceh Regency. Based on the results of the t test the Dummy vari- able obtained a t-count value greater than the t table, it can be con- cluded that extreme economic assistance has a significant positive relationship to community income in Kaway XVI District, West Aceh Regency. In the regression results the R-squared value is 0.360154. Where 36.02% of the variation in community income can be explained by the model (dummy variable assistance (D1) and the amount of extreme economic assistance (X)). The rest (63.98%) is explained by other factors not included in the model.